Muskuloskelettal Medicine - Gureck AE; Schon J; Rhim HC; Wasserman L; Hollander K; Tenforde AS (Deutsche Zeitschrift für Sportmedizin)
Problem: The first metatarsophalangeal (MTP) joint can become painful in runners and limit ability to remain active. Extracorporeal shockwave therapy (ESWT) is a conservative treatment option for musculoskeletal disorders due to its proposed effect on tissue remodeling and pain modulation and is best combined with physical therapy (PT). We hypothesized that a portion of runners with first MTP pain treated with ESWT and PT would achieve functional improvements.Methods: Chart review identified 21 runners who received ESWT and PT for first MTP joint pain. Functional outcomes were quantified using the Foot and Ankle Ability Measure (FAAM) prior to and following treatment, and patients meeting minimally clinically important differences (MCID) was the primary outcome of interest. Each runner received a minimum of three sessions of ESWT over the MTP joint, and PT focused on intrinsic foot strengthening and joint mobilization.Results: MCID was achievable in either FAAM ADL and/or FAAM Sports subscales for 15 of 21 runners, of whom 9 of 15 (60%) met MCID in one or both subscales. FAAM Sports subscale improved from pre-treatment median of 12 to best post-treatment median of 23 (p=0.0049) after a median time of 3 weeks.Discussion: ESWT combined with PT may be an effective and well-tolerated treatment for runners with first MTP joint pain in whom other conservative management has failed. Most included runners treated with ESWT and PT had improved function. Key Words: Foot, Running, Rehabilitation